"Luxury beliefs": Signaling through ideology? - Margaret Samahita (University College Dublin, UCD School of Economics, 2024)
The concept of "luxury beliefs" has gained increasing attention in recent months. It captures the idea that, as status goods become more affordable, ideology has emerged as a new way to signal status. I use a signaling game to derive a prediction related to the concept: given some beliefs are associated with high status, lower status individuals seek to pool with high status individuals by stating these beliefs if the social image gain is sufficiently high. I test this prediction using two online experiments and a series of statements commonly recognised as "luxury beliefs". I find that i) luxury beliefs are not strongly associated with status: they are only perceived to signal college attendance and negatively correlate with income and perceived income; and ii) there is no evidence of signaling using these beliefs in a (close to anonymous) online setting.
Keywords: C90; D83; Z13; 330; luxury beliefs; status signaling; social image